Examination of the relationship between the self-efficacy and decision-making styles of wrestling referees - Musab Cagin; Sezen Cimen Polat; Selim Aslan; Halil Ibrahim Cicioglu (Ozlem Book Center, 2024)
The present study aims to determine and comparatively examine the relationship between the self-efficacy and decision-making styles of wrestling referees. In the research, the relational screening model, one of the quantitative models, was used, and the criterion sampling method, one of the purposeful sampling methods, was used in sampling selection. A total of 106 man referees, 77 national and 29 international, participated in the study. The mean age of the participating referees was 39.18±7.60 years, and the mean years of wrestling refereeing was 13.62±7.53 years. The decision-making styles of the wrestling referees were measured using the Melbourne Decision Making Questionnaire and their self-efficacy was measured using the Referee Self-Efficacy Scale. Cronbach's Alpha coefficients of the scales were determined as 0.78 for the Melbourne Decision Making Scale and 0.92 for the Referee Self-Efficacy Scale. The data obtained were transferred to the SPSS 26.0 program and the Pearson Correlation Analysis, Independent Samples T-Test, One-Way ANOVA and descriptive statistics were applied. According to the findings of the study, there was a significant positive correlation between the self-efficacy scores of the referees and their self- esteem in decision-making and careful decision-making scores, and a significant negative correlation between the suspensive and panic decision-making scores (p<0.05). In conclusion, it was determined that as referee self-efficacy increased, the level of self-esteem in decision-making and careful decision-making increased, and the level of suspensive and panic decision-making decreased.